HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN MINAT KUNJUNGAN KE POSYANDU DI DESA HASAHATAN JAE KABUPATEN PADANG LAWAS - Imsaruddin, Guntur; Martua, Tohong (Universitas Aufa Royhan, 2016)
Efforts to accelerate the reduction in infant mortality and maternal mortality rates, would be successful if all stakeholders engage both members of the government or elements of society and the business world. From the analysis of the data found that the support of the family of 40 respondents showed respondents with good knowledge with interest the visit to the Posyandu is 16 people (40.00%) Category Just 16 people (40.00%) and less than 8 people (20.00 %). While the category of positive attitude as much as 27 people (67,50), whereas negative attitudes there are 13 people (32.50%). And while the high interest category No 27 (67.50), while the low interest there are 13 people (32.50%). Based on the results obtained chi-square test p-value = 0.00. From these results it can be concluded that the p-value <α (0.05) or 0.00 <0,05 so Ho rejected and Ha accepted, meaning there is a relationship between Knowledge and Attitude Mother With interest Visits to IHC. Advised on health centers and health advice in the location for more meningkatkkan quality research and education on public health.